Male Sexual Behavior and Pheromone Emission Is Enhanced by Exposure to Guava Fruit Volatiles in Anastrepha fraterculus - Bachmann, Guillermo Enrique (2015)
Background: Plant chemicals can affect reproductive strategies of tephritid fruit flies by influencing sex pheromone communication and increasing male mating competitiveness. Objective and Methodology: We explored whether exposure of Anastrepha fraterculus males to guava fruit volatiles and to a synthetic blend of volatile compounds released by this fruit affects the sexual performance of wild and laboratory flies. By means of bioassays and pheromone collection we investigated the mechanism underlying this phenomenon. Results: Guava volatile exposure enhanced male mating success and positively affected male calling behavior and pheromone release in laboratory and wild males. Changes in male behavior appear to be particularly important during the initial phase of the sexual activity period, when most of the mating pairs are formed. Exposure of laboratory males to a subset of guava fruit volatiles enhanced mating success, showing that the response to the fruit might be mimicked artificially. Conclusions: Volatiles of guava seem to influence male mating success through an enhancement of chemical and physical signals related to the communication between sexes. This finding has important implications for the management of this pest species through the Sterile Insect Technique. We discuss the possibility of using artificial blends to improve the sexual competitiveness of sterile males.